A PRISMA systematic review of adolescent gender dysphoria literature: 2) mental health - Lucy Thompson; Darko Sarovic; Philip Wilson; Angela Sämfjord; Christopher Gillberg (Public Library of Science (PLoS), 2022)
It is unclear whether the literature on adolescent gender dysphoria (GD) provides sufficient evidence to inform clinical decision making adequately. In the second of a series of three papers, we sought to review published evidence systematically regarding the extent and nature of mental health problems recorded in adolescents presenting for clinical intervention for GD. Having searched PROSPERO and the Cochrane library for existing systematic reviews (and finding none), we searched Ovid Medline 1946 -October week 4 2020, Embase 1947-present (updated daily), CINAHL 1983-2020, and PsycInfo 1914-2020. The final search was carried out on the 2nd November 2020 using a core strategy including search terms for 'adolescence' and 'gender dysphoria' which was adapted according to the structure of each database. Papers were excluded if they did not clearly report on clinically-likely gender dysphoria, if they were focused on adult populations, if they did not include original data (epidemiological, clinical, or survey) on adolescents (aged at least 12 and under 18 years), or if they were not peer-reviewed journal publications. From 6202 potentially relevant articles (post deduplication), 32 papers from 11 countries representing between 3000 and 4000 participants were included in our final sample. Most studies were observational cohort studies, usually using retrospective record review (21). A few compared cohorts to normative or population datasets; most (27) were published in the past 5 years. There was significant overlap of study samples (accounted for in our quantitative synthesis). All papers were rated by two reviewers using the Crowe Critical Appraisal Tool v1·4 (CCAT). The CCAT quality ratings ranged from 45% to 96%, with a mean of 81%. More than a third of the included studies emerged from two treatment centres: there was considerable sample overlap and it is unclear how representative these are of the adolescent GD community more broadly. Adolescents presenting for GD intervention experience a high rate of mental health problems, but study findings were diverse. Researchers and clinicians need to work together to improve the quality of assessment and research, not least in making studies more inclusive and ensuring long-term follow-up regardless of treatment uptake. Whole population studies using administrative datasets reporting on GD / gender non-conformity may be necessary, along with inter-disciplinary research evaluating the lived experience of adolescents with GD.